Acceptance Towards COVID-19 Vaccination in Breast Cancer Patients: An Analytical Cross-Sectional Study in A Tertiary Care Hospital of Rawalpindi, Pakistan - Malik, Asmara Ahmed; Zubaida Rashid; Syeda Rifaat Qamar Naqvi; Mommana Ali Rathore; Nadia Ramzan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the level of COVID-19 vaccine acceptance among patients diagnosed with breast cancer. Study Design: Analytical cross-sectional. Place and Duration of Study: The study was conducted in Breast Cancer Outpatient Department located in a tertiary care hospital in Rawalpindi, Pakistan from Nov 2021 to Jul 2022. Methodology: Validated questionnaire was used to collect data from patients diagnosed with breast cancer. Sample size of n=134 was attained using non-probability consecutive sampling. Data was analyzed using SPSS version 22. A p-value of <0.05 was taken as significant. Outcome assessed was whether breast cancer patient’s personal level of knowledge, mindset, motivation, and concerns towards getting about COVID-19 vaccination helped or hindered their acceptance of COVID-19 vaccination. Results: COVID-19 vaccine acceptance was found among 124(92.5%) breast cancer patients. Social media and means of mass communication such as television were significant sources of information for COVID-19 related vaccine information (p<0.05). A strong positive correlation was found between Total Vaccine Acceptance Score with domains of Knowledge (r=0.353, p<0.000), Mindset (r=0.662, p< 0.000), Motivation (r=0.780, p< 0.000) and Concerns (r=0.800, p< 0.000). Higher awareness with positive motivators and mindset of participants lead to greater acceptance of COVID-19 vaccines despite breast cancer diagnosis. Conclusion: High vaccine acceptance was found among breast cancer patients. High scores of COVID-19 disease knowledge, positive mindset and high motivation towards COVID-19 vaccines leading to a higher overall vaccine acceptance.